MEDIA SOSIAL DAN HOAX DALAM DUNIA PELAJAR ASRAMA SUSTERAN PUTERI KASIH “MARGARET NASSEAU” MALANG 2019 - Galan Suswardana (Arete, 2020)
This study focuses on social media and hoax. The writer argues that hoax has huge effects on language structure in social media, especially on the truth that is delivered in social media language. Languages that are delivered in social media include both verbal and non-verbal. In order to know the truth in the language used in social media, careful observation is needed. This statement is strengthened by Emanuel Kant who says that something that is disclosed in a certain language is never a pure object that is stand alone, neutral, and autonomous. Truth always depends on the mindset and diction of a human as a subject. This implied that every language in social media is not neutral and autonomous. Here, the writer concludes that truth in social media language is not absurd moreover if the language is only written for personal interest that puts aside real truth like a hoax. Therefore, philosophical language analysis is needed to analyze truth in social media.